Leitura em trânsito: uma aproximação com as práticas de produção, difusão e leitura do jornal Super Notícia - Renata Kelly de Arruda (2009)
This study focus on the analysis of Super Notícia newspaper, a daily publishing in Belo Horizonte, from Sempre Editora LTDA. The newspaper is targeted at popular audience and since 2006 has reached a growing in sales without any preeceding in the national journalistic scenario. The research analyzes issues related to the media and its content, ways of production, announcing, sale and gets closer to the readers and their reading practices. It uses a qualitative methodology, with documental analysis, interviews, questionnaires and direct observation of reading practices. Its multidisciplinary characteristic is found in the fields of Education, Science Information, Social Communication and Language. The History and Sociology field also contributes to the development of the study thorough Chartier, Bordieau. Mollier, Darnton and researchs about journal editions, such as the ones of Isabel Frade. The results shows that Super Notícia newspaper with its special features such as easy access, easy format, language and a varied content, has made its readers closer and it seems to present a new moment in the reading practices undertaken in the urban spaces. The research points out some strategies used by editors that unfold their knowledge about the process of creating new readers. The interviews also points out that some sales strategies that were disappearing are coming back in the journalistic field. The field observation and its writing of reading practices in the streets of Belo Horizonte present free readings, the relation between body and stand, the non canonic reading practices in a city's daily life full of sounds and movements. The reader is represented in the newspaper through the geographic proximity of the news, the production of some sections in which the reader can give opinion, the services offered and the solving of some demands. The subject's objectivity, the short written style and a narrative close to the oral language also contributes to the proximity and complicity between the text and the reader.